(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Dexamethasone is a highly potent glucocorticoid. Treatment with dexamethasone results in several metabolic perturbations on nearly all organs of the body including the liver. Objective:This study had been carried out in order to investigate the effects of dexamethasone sodium phosphate as synthetic form of glucocorticoids on the rabbit liver as a model for human liver, by a light microscope, using two extreme of doses and two durations to show the dose and duration dependency. Methods: Liver specimens were obtained from rabbits treated with dexamethasone sodium phosphate and from control groups 1 and 2, the specimens were fixed and processed to evaluate the histological and histochemical changes. Results: Vacuolation and ballooning of hepatic cells were observed in the liver of the treated groups associated with degenerative changes of these cells, dilatation and congestion of central hepatic vein and sinusoidal capillaries were observed, positive periodic acid schiff’s stain (PAS) reactions were noticed in the treated groups. All these changes were dose and duration related. Conclusion:Morphological changes induced in the liver by dexamethasone sodium phosphate could be accepted as side effects of these drugs. Key words:Liver, dexamethasone, histology, glycogen.